Impact of Equity Capital on the profitability of Nepalese Commercial Banks - Thagunna, Prakash; Thakuri, Pratibha; Thapa, Rabina; Chaudhary, Raman Kumar; Dahal, Roshan; Das, Roshan Kumar (Nepalese Journal of Finance, 2025)
This study examines the impact of equity capital on the profitability of Nepalese commercial banks. Return on assets and return on equity are the selected dependent variables. The selected independent variables are capital adequacy ratio, equity to assets ratio, debt ratio, deposit to assets ratio, loan to deposit ratio and bank size. The study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2015/16 to 2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of equity capital on the profitability of Nepalese commercial banks. The results showed that bank size has a positive impact on return on assets and return on equity. It means that increase in bank size leads to increase in return on assets and return on equity. Similarly, capital adequacy ratio has a positive impact on return on assets and return on equity. It means that increase in capital adequacy ratio leads to increase in return on assets and return on equity. In contrast, deposit to assets ratio has a negative impact on return on assets and return on equity. It means that increase in deposit to assets ratio leads to decrease in return on assets and return on equity. Likewise, debt ratio has a negative impact on return on assets and return on equity. It shows that higher the debt ratio, lower would be the return on assets and return on equity. Moreover, loan to deposit ratio has a positive impact on return on assets and return on equity. It indicates that increase in loan to deposit ratio leads to increase in return on assets and return on equity. Further, equity capital ratio has a positive impact on return on assets and return on equity. It indicates that increase in equity capital ratio leads to increase in return on assets and return on equity.